2010
DOI: 10.1007/s11060-010-0457-5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing age at diagnosis and worsening renal function in patients with primary central nervous system lymphoma

Abstract: High-dose Methotrexate (MTX) is the most useful cytotoxic drug used in the treatment of primary central nervous system lymphoma (PCNSL). Dose reduction should be made in patients with reduced renal function. We evaluated the age of patients over a period of 22 years and estimated their glomerular filtration rate. One hundred and two patients were treated in Nottingham University Hospitals (a regional centre for neurosurgery) during the period 1986-2008. Patients were treated either with the BVAM regimen (carmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The median age of our patients was 50 years, which is about a decade younger than that reported in Western literature (Bataille et al, 2000;Bessell et al, 2011). An earlier multi-centric hospital based study from India had also showed that PCNSL occurs a decade earlier in Indian patients and is only very rarely associated with AIDS (Sarkar et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
“…The median age of our patients was 50 years, which is about a decade younger than that reported in Western literature (Bataille et al, 2000;Bessell et al, 2011). An earlier multi-centric hospital based study from India had also showed that PCNSL occurs a decade earlier in Indian patients and is only very rarely associated with AIDS (Sarkar et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
“…With the median age at diagnosis of PCNSL rising above 63 years [83, 84] and over 20 % patients older than 80 years [85], establishing optimal treatment in older patients is of paramount importance. The true incidence may be underestimated if there is reluctance to biopsy cerebral lesions in this age group, as the possible treatment options are considered to be limited.…”
Section: Treatmentmentioning
confidence: 99%
“…Symptoms can be misinterpreted in older patients resulting in significant treatment delays [86]. Altered metabolism of cytotoxic drugs [38] and impaired organ function [83] present additional therapeutic challenges.…”
Section: Treatmentmentioning
confidence: 99%
“…1,2 Median age at diagnosis has increased from 60.5 to 65 years during the last 20 years. 3 In 2002, the Nordic Lymphoma Group published a phase ll trial investigating whether an age-adjusted regimen consisting of chemotherapy alone could induce durable remissions in PCNSL patients. 4 The responses achieved were of short duration.…”
Section: Introductionmentioning
confidence: 99%